Laboratory Study of the Influence of Substrate Type and Temperature on the Exploratory Tunneling by Formosan Subterranean Termite - Gautam, Bal K. (Insects, 2012)
Using two-dimensional foraging arenas, laboratory tests were conducted to investigate the effect of soil type, soil moisture level and ambient temperature on the exploratory tunneling by Coptotermes formosanus Shiraki. In choice arenas consisting of two substrate types having two moisture levels each, and conducted at a constant temperature of 22 °C, a significantly greater proportion of termites aggregated in sand than in sandy loam. Similarly, the length of excavated tunnels was also increased in sand. In a given substrate, termite aggregation or tunnel length did not differ between 5% and 15% moisture levels. In no-choice tests, where three different substrates (sand, sandy loam and silt loam) were tested at two temperatures (22 °C and 28 °C), excavations were significantly greater in sand than either sandy loam or silt loam at 22 °C. Fewer primary tunnels were constructed in sandy loam than in sand and fewer branched tunnels than either in sand or silt loam. No significant difference in either tunnel length or number of primary or branched tunnels was found between these two temperatures.